Decolorization and Degradation of a Mixture of Industrial Azo Dyes by Anodic Oxidation Using a Ti/Ru0.3ti0.7o2 (Dsa-Cl2) Electrode - Salazar-Gonzalez, R; Vidal-Fuentes, J; Vidal-Fuentes, J; Espinoza-Cisternas, L; Espinoza-Cisternas, L; Sandoval, A; Sandoval, A (Wiley-Blackwell, 2019)
The electrochemical treatment of wastewaters from the textile industry is a promising alternative for the elimination of organic pollutants. This study approach the decolorization and chemical oxygen demand (COD) removal from synthetic water (0.91 mM Acid Yellow 25 dye - and - 0.42 mM Acid Blue 29 dye), by anodic oxidation (AO) in batch mode using a Ti/Ru0.3Ti0.7O2 (DSA-Cl2) electrode as anode and an AISI 304 stainless steel plate as cathode. The influence of pH (3, 7 and 10), type of supporting electrolyte (50 mM Na2SO4, 50 mM NaCl and 100 mM NaCl) and applied current density (10 < j < 80 mA cm–2) on COD removal and mineralization current efficiency was analyzed. The best AO test in terms of energy consumption was performed at pH 7, 50 mM NaCl and j=30 mA cm–2, obtaining a complete decolorization and COD removal. These operating parameters have an energy consumption between 0.41 and 0.82 kWh m–3. High performance liquid chromatography (HPLC-MS/MS) analyses indicated the presence of several organic intermediates and carboxylic acids. © 2019 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim